1991
DOI: 10.1111/j.2042-7158.1991.tb06662.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Radiolabelled Saccharin Solution to Monitor the Effect of the Preservatives Thiomersal, Benzalkonium Chloride and EDTA on Human Nasal Clearance

Abstract: The effect of thiomersal, benzalkonium chloride and ethylenediaminetetraacetic acid (EDTA) on the nasal mucociliary clearance of healthy volunteers has been investigated using a modified saccharin test and gamma scintigraphy concomitantly. A significant correlation was found between the two techniques. Using each subject as his/her own control, none of the preservatives significantly altered the rate of clearance or proportion cleared from the nasal cavity after the administration of a single dose. This result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In the presence of CCM, the absorption of 15-159 was fast, as evidenced by a median t max that ranged between 10 and 20 min for the different dose groups. This finding is in agreement with a previous study in which a value of 15 min was reported [13] and is consistent with absorption through the nasal mucosa [17]. The pharmacokinetics of alnitidan [18], an investigational5-HT 1BIl D receptor agonist, and sumatriptan [19,20] were also investigated after intranasal administration.…”
Section: Discussionsupporting
confidence: 81%
“…In the presence of CCM, the absorption of 15-159 was fast, as evidenced by a median t max that ranged between 10 and 20 min for the different dose groups. This finding is in agreement with a previous study in which a value of 15 min was reported [13] and is consistent with absorption through the nasal mucosa [17]. The pharmacokinetics of alnitidan [18], an investigational5-HT 1BIl D receptor agonist, and sumatriptan [19,20] were also investigated after intranasal administration.…”
Section: Discussionsupporting
confidence: 81%
“…This is consistent with absorption through the nasal mucosa in accordance with the mucociliary clearance under physiologic conditions. 20 In contrast, sumatriptan shows a t max from 1 to 1.5 hours, which reflects the fact that sumatriptan after nasal administration is swallowed to a great extent and subsequently absorbed from the gastrointestinal tract. 21,22 Nasal administration of dihydroergotamine also yields a t max of approximately 1 hour.…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples of 5 mL for pharmacokinetics were collected, by means of a catheter inserted into a forearm vein, into glass tubes containing ethylenediamine tetraacetic acid as anticoagulant just before and at 5,10,15,20,25,30,35,40, and 50 minutes and at 1, 1.5, 2, 2.5, 3, 4, 5, 6, 7, 8, 10, and 12 hours after drug administration. Within 15 minutes of collection, the blood samples were spun in a centrifuge, and plasma was carefully separated.…”
Section: Assessmentsmentioning
confidence: 99%
“…This fraction is rapidly cleared to the nasopharynx within 15-30 minutes by mucociliary clearance and sni ng (Batts et al, 1991;Lansley, 1993;Weisman et al, 2012). However, a large remainder is deposited on the sparsely ciliated transitional mucosa and non-ciliated epithelium in the anterior vestibule, from where it is slowly cleared to the nasopharynx over the course of several hours (Djupesland et al, 2013;Leach et al, 2015).…”
Section: Saliva Oxytocin Concentrations Do Not Reflect Plasmamentioning
confidence: 99%